Inclusive education in the discourse of hypocrisy - Amadeusz Krause (Studia z Teorii Wychowania)
The article presents the problems of assumptions of inclusive education. Some of the assumptions appear hypocritical, where declarations of inclusion are accompanied by an exclusionary discourse. These discourses are analyzed in the light of the development of the theory of special education and in the actions of educational officials and politicians. Particular attention was paid to the “Education for All” project. The author points out that this project, despite valuable declarations, contains in the executive part a traditional, clinical image of person with disabilities. This image is not conductive to the inclusion of children in joint education.